Three-component coupling involving arynes, aromatic tertiary amines, and aldehydes via aryl-aryl amino group migration - Bhojgude, Sachin Suresh; Baviskar, Dnyaneshwar R.; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2015)
The transition-Metal-free multicomponent coupling of arynes, aromatic tertiary amines, and aldehydes proceeding via the aryl to aryl amino group migration has been demonstrated. This protocol allows rapid access to ortho-functionalized tertiary amines in moderate to good yields. Moreover, activated ketones can also be used as the aldehyde Component in the present reaction. The similarity of the aryl-aryl tertiary amino group migration with the Smiles rearrangement is striking.